Factors associated with more frequent diagnostic tests and procedures in patients with irritable bowel syndrome. (January 2019) - Lacy, Brian; Ayyagari, Rajeev; Guerin, Annie; Lopez, Andrea; Shi, Sherry; Luo, Michelle
Background: Irritable bowel syndrome (IBS) reduces quality of life and burdens healthcare systems. This study identified factors associated with frequent use of IBS diagnostic tests and procedures. Methods: Using a United States claims database (2001–2012), tests and procedures in IBS patients occurring in the 2-year study period (12 months before/following the first IBS diagnosis) were analyzed: endoscopy, GI transit testing, anorectal procedures, and radiologic imaging. Patients were classified based on test/procedure frequency (3+, 1–2, or 0). Multivariate logistic regression identified factors associated with more frequent tests/procedures. Results: Among 201, 322 IBS patients, 41.7% had 3+ tests/procedures, 35.1% had 1–2, and 23.3% had 0. Patients with more tests/procedures were older [mean age 50.6 (3+ group), more likely to be female and had more comorbidities, including anxiety, depressive disorders, and somatization. Dyspepsia [odds ratio (95% confidence interval): 1.80 (1.72–1.87)], interstitial cystitis [1.60 (1.45–1.77)], gastroesophageal reflux disease [1.59 (1.55–1.63)], constipation [1.50 (1.45–1.54)], and dyspareunia [1.38 (1.25–1.52)] were significantly associated with more tests/procedures (3+ versus 1–2), while anxiety, depressive disorders, and somatization were not. Patients with more frequent specialist visits [emergency department (ED; 1.10 (1.09–1.11)) and gastroenterologists (1.26 (1.26–1.27))] or at least one GI-related ED visit or inpatient admission [1.95 (1.86–2.04) and 3.67 (3.48–3.87), respectively] were more likely to have more tests/procedures (all p < 0.05). Conclusions: Test frequency in patients with IBS is strongly associated with demographic and clinical characteristics, especially comorbid conditions related to IBS. Presence of common overlapping comorbid conditions should increase clinicians' confidence in making the diagnosis of IBS, thus curtailing redundant testing and reducing healthcare costs.